Peach palm flour (Bactris gasipae KUNTH): potential application in the food industry - PIRES,Márlia Barbosa (2019)
Abstract Peach palm flours prepared from the landraces microcarpa (MIF), mesocarpa (MEF), and macrocarpa (MAF) were assessed for their functional and morphological characteristics. The flours had moisture contents in accordance with the current legislation, considerable lipid (≥3.95%) and carbohydrate (≥66.68%) contents, and potential as an energy source (≥300 kcal/100 g). MEF and MAF can be considered rich in dietary fibers since their fiber contents were above 6 g/100 g, which contributes to the nutritional enrichment of products prepared with those flours. The assessment of the technological properties, WAC (≥255%) and OAC (≥65%) showed the peach palm flours can be used as raw material in different products such as breads, cakes, meat products, and breaded foods, thus adding energy, nutritional, and economic value. It is worth pointing out that peach palm is gluten free, hence it is an option for the development of new products targeted at consumers with celiac disease.